2011
DOI: 10.2147/copd.s22896
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the impact of high-frequency chest wall oscillation in chronic obstructive pulmonary disease patients with mucus hypersecretion

Abstract: IntroductionChronic obstructive pulmonary disease (COPD) patients with mucus hypersecretion tend to demonstrate increased frequency of infective exacerbations and a steeper slope of decline in lung function. Enhanced mucociliary clearance with high-frequency chest wall oscillation (HFCWO) devices previously used in cystic fibrosis and bronchiectasis patients may offer the opportunity for community-based, self-managed therapy to improve quality of life and lung function.Study design and methodsA randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 28 publications
2
43
0
2
Order By: Relevance
“…4,6,12,23 Our results also coincide with pilot study carried out by Chakravorty et al whom reported that patients with AECOPD and mucus hypersecretion are at increased risk of declining lung function, tolerated the HFCWO treatment well, leading to improvement in CAT-score and quality of life and reduced symptoms. 7 Moreover; our result is consistent with Mahajan et al, who stated that HFCWO is well tolerated in adults hospitalized for AECOPD or acute asthma and significantly improves dyspnea, also reported that patient with AECOPD use fewer antibiotics, due to fewer respiratory infections with less hospitalization. 23 In order to evaluates the tolerance to exertion as an equivalent to physical fitness, we used therapeutic effects of vest HFCWO and Flutter groups on the BODE index and its components, there was significant improvement of BODE index, 6-MWD, MMRC scale in HFCWO and Flutter groups, while BMI did not show any significant difference in both groups.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…4,6,12,23 Our results also coincide with pilot study carried out by Chakravorty et al whom reported that patients with AECOPD and mucus hypersecretion are at increased risk of declining lung function, tolerated the HFCWO treatment well, leading to improvement in CAT-score and quality of life and reduced symptoms. 7 Moreover; our result is consistent with Mahajan et al, who stated that HFCWO is well tolerated in adults hospitalized for AECOPD or acute asthma and significantly improves dyspnea, also reported that patient with AECOPD use fewer antibiotics, due to fewer respiratory infections with less hospitalization. 23 In order to evaluates the tolerance to exertion as an equivalent to physical fitness, we used therapeutic effects of vest HFCWO and Flutter groups on the BODE index and its components, there was significant improvement of BODE index, 6-MWD, MMRC scale in HFCWO and Flutter groups, while BMI did not show any significant difference in both groups.…”
Section: Discussionsupporting
confidence: 91%
“…4 Conversely, Chakravorty et al, found no significant change in baseline spirometricindices (FEV1 or FVC) with HFCWO versus postintervention ones. 7 Mahajan et al, and Holland et al, reported that the vest HFCWO device was well tolerated with improvement in ventilatory functions. 23,28 The patients often feel better because they don't have to struggle to breathe and feel less fatigued, so improving quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 To reduce the rate of treatment failure, different integrated strategies have been successfully implemented during NIV in expert RICU and ICU settings, such as careful pharmacologic sedation to improve a patient's cooperation, 9 early fiberoptic bronchoscopy, and/or high-frequency chest wall compressions (HFCWC) to promptly remove the excessive burden of secretion in COPD subjects with respiratory muscle fatigue and ineffective cough. 10,11 Extracorporeal CO 2 removal, which developed from the traditional extracorporeal membrane oxygenation, 12,13 has been recently proposed as an alternative or an integrated therapeutic option in patients with acute hypercapnic acidotic respiratory failure who are non-responders to an NIV trial. 14,15 Although extracorporeal membrane oxygenation is a total extracorporeal support that is able to oxygenate severely hypoxemic patients and remove up to 50% of the total body CO 2 production, extracorporeal CO 2 removal works as a partial extracorporeal support capable of removing lower amounts of CO 2 without substantial effects on oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been described to improve the expiratory phase and avoid premature airway closure in obstructive subjects; 6,[17][18][19][20] one such technique is ELTGOL. The slow expiration with open glottis performed during ELTGOL increases expiratory time.…”
Section: Discussionmentioning
confidence: 99%